2018
DOI: 10.1038/s41541-018-0065-5
|View full text |Cite
|
Sign up to set email alerts
|

Antibody targeting of a specific region of Pfs47 blocks Plasmodium falciparum malaria transmission

Abstract: Transmission-blocking vaccines are based on eliciting antibody responses in the vertebrate host that disrupt parasite development in the mosquito vector and prevent malaria transmission. The surface protein Pfs47 is present in Plasmodium falciparum gametocytes and female gametes. The potential of Pfs47 as a vaccine target was evaluated. Soluble full-length recombinant protein, consisting of three domains, was expressed in E. coli as a thioredoxin fusion (T-Pfs47). The protein was immunogenic, and polyclonal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 23 publications
(30 reference statements)
4
67
0
Order By: Relevance
“…A recent study has shown that antibodies binding a 52 amino acid region of Pfs47 confer strong transmission blocking of laboratory P. falciparum strains in A. gambiae [42]. In the same study, antibodies binding different regions of the protein showed either weak or no transmission blocking activity, consistent with an earlier study reporting that none of three monoclonal antibodies against Pfs47 could affect P. falciparum infections in A stephensi [43].…”
Section: Resultssupporting
confidence: 84%
“…A recent study has shown that antibodies binding a 52 amino acid region of Pfs47 confer strong transmission blocking of laboratory P. falciparum strains in A. gambiae [42]. In the same study, antibodies binding different regions of the protein showed either weak or no transmission blocking activity, consistent with an earlier study reporting that none of three monoclonal antibodies against Pfs47 could affect P. falciparum infections in A stephensi [43].…”
Section: Resultssupporting
confidence: 84%
“…The monoclonal antibodies initially available against Pfs47 did not exhibit TB activity (83), and therefore, Pfs47 had not been the focus of much previous analysis. However, the transmission-blocking potential of Pfs47 has been demonstrated recently (43).…”
Section: Gametocyte/gamete Antigens Pfs230 Pfs48/45 Pfs47 and Hap2mentioning
confidence: 99%
“…This problem was overcome by expressing a section of domain 2 (aa 178 to 267) in which the two cysteines were replaced with alanines (mD2). The original MAbs generated against full-length protein did not recognize the recombinant, so mD2 was used to generate additional MAbs, some of which were found to have significant TRA, inhibiting fertilization and subsequent ookinete formation (43). Further analysis of domain 2 identified a smaller, relatively conserved 52-aa region (aa 178 to 229) that elicited TRA antibodies in mice, and this is currently a prospective transmission-blocking vaccine candidate.…”
Section: Gametocyte/gamete Antigens Pfs230 Pfs48/45 Pfs47 and Hap2mentioning
confidence: 99%
See 1 more Smart Citation
“…transmission blocking vaccines (TBVs), or transmission blocking drugs (TBDs) against parasitic sexual stages [9]. Antibodies targeted to three of the five currently proven, potent TBV targets have confirmed localization to proteins found on the surface of the plasma membrane of the gametes [10-20], clearly indicating the potential value of targeting this stage of the parasite lifecycle. Additionally, multiple anti-malarial compounds have been demonstrated to have activity against this parasitic stage [21-25].…”
Section: Introductionmentioning
confidence: 99%